Peripheral changes of endocannabinoid system components in episodic and chronic migraine patients: A pilot study - Greco, Rosaria; Demartini, Chiara; Zanaboni, Anna Maria; Tumelero, Elena; Icco, Roberto De; Sances, Grazia; Allena, Marta; Tassorelli, Cristina (Cephalalgia, 2021)
Background Preclinical and clinical evidence suggests a role for the dysregulation of the endocannabinoid system in migraine pain, particularly in subjects with chronic migraine. Methods The gene expression of endocannabinoid system components was assayed in peripheral blood mononuclear cells of 25 subjects with episodic migraine, 26 subjects with chronic migraine with medication overuse (CM-MO) and 24 age-matched healthy controls. We also evaluated the protein expression of cannabinoid receptors 1 and 2 as well as DNA methylation changes in genes involved in endocannabinoid system components. Results Both episodic migraine and CM-MO subjects showed higher cannabinoid receptor 1 and cannabinoid receptor 2 gene and protein expression compared to controls. Fatty acid amide hydrolase gene expression, involved in anandamide degradation, was lower in migraine groups compared to healthy control subjects. N-arachidonoyl phosphatidylethanolamine phospholipase D gene expression was significantly higher in all migraineurs, as were monoacylglycerol lipase and diacylglycerol lipase gene expressions. The above markers significantly correlated with the number of migraine days and with the days of acute drug intake. Conclusion The findings point to transcriptional changes in endocannabinoid system components occurring in migraineurs. These changes were detected peripherally, which make them amenable for a wider adoption to further investigate their role and applicability in the clinical field. clinicaltrials.gov NTC04324710.